2018
DOI: 10.3389/fendo.2018.00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Deficiency on Incidence Risk of Gestational Diabetes Mellitus: A Systematic Review and Meta-analysis

Abstract: IntroductionProper nutrition is important for overall health, and it reduces healthcare costs associated with malnutrition. Many studies have investigated vitamin D deficiency and its role in gestational diabetes and controversial data have reported. A comprehensive consideration of articles in this field provides the possibility of a general study of this relationship. This meta-analysis is an evaluation of the relationship between vitamin D deficiency and gestational diabetes.Material and methodsDifferent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 62 publications
2
49
0
4
Order By: Relevance
“…Similar observations were made by Al-Ajlan et al in Saudi Arabian women [119]. There are some well-performed systematic reviews and meta-analyses about the above-mentioned problem -in both of them lower vitamin D levels were found to be associated with the increased risk of developing GDM [65,[120][121][122][123]. According to the meta-analysis by Palacios et al, vitamin D deficiency in early pregnancy was associated with elevated risk of developing GDM [27].…”
Section: Gestational Diabetes Mellitussupporting
confidence: 71%
“…Similar observations were made by Al-Ajlan et al in Saudi Arabian women [119]. There are some well-performed systematic reviews and meta-analyses about the above-mentioned problem -in both of them lower vitamin D levels were found to be associated with the increased risk of developing GDM [65,[120][121][122][123]. According to the meta-analysis by Palacios et al, vitamin D deficiency in early pregnancy was associated with elevated risk of developing GDM [27].…”
Section: Gestational Diabetes Mellitussupporting
confidence: 71%
“…Several investigations have shown that low serum 25(OH)D concentrations are associated with some adverse neonatal and pregnancy outcomes [ 65 , 66 , 67 , 68 ]. In this context, several reviews and meta-analyses support the notion that low serum 25(OH)D concentrations are a risk factor for hypertensive disorders in pregnancy such as pre-eclampsia, and for gestational diabetes mellitus [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Moreover, in the majority of the published meta-analyses low serum 25(OH)D concentration in pregnant women are associated with an increased risk of their children for childhood asthma, wheeze, respiratory tract infections, allergic rhinitis, and eczema [ 79 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…If the solar ultraviolet B radiation is low, production of vitamin D in the skin will remain low exposing the individual to lower blood vitamin D levels. Further, low blood vitamin D levels have been shown to be a risk factor for GDM [18,19]. It has been suggested that vitamin D mediates the onset of GDM by regulating the immune system and inflammatory responses, oxidative stress, blood calcium level, hepatic metabolism, as well as with the function and development of pancreatic islets [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent systematic reviews, low vitamin D levels in pregnant women seem to be associated with GDM [18,19]. Main sources for vitamin D are sunshine and fish oil [20].…”
Section: Introductionmentioning
confidence: 99%